Metanálise de Relações Interpessoais no Método de Rorschach em Países Ocidentais - Rafael Rubens de Queiroz Balbi Neto; Sávio Silveira de Queiroz (Interpersona: An International Journal on Personal Relationships, 2011)
The aim of this study is to do a metanalysis of variables indicative interpersonal relationships result (HVI, Hypervigilance Index, CDI, Coping Deficit Index, SumT, Sum of the Texture’s answers, COP, Cooperative Movement, AG, Aggressive Movement, p, Active Movement and, a, Passive Movement) in 14 western countries (Italy, Argentina, Greece, Finland, Denmark, Belgium, Australia, United States, Spain, Romania, Portugal, Peru, Holland and Brazil). For that, 16 Normative’s papers of the Rorschach Comprehensive System were analyzed, comparing eleven different measures among the 14 countries (HVI positive, CDI=5, CDI=4, CDI positive, SumT=0, SumT>1, COP=0, COP>2, AG=0, AG>2 e p>a+1). The results are pointing that the Brazilian sample is above 01 standard deviation for the following measures: CDI=5, CDI=4, CDI positive, AG=0 e p>a+1. Brazil also presents the largest measure for: CDI=5, CDI=4, CDI positive e AG=0. The data indicate that the Brazilian sample have more difficulty contending with the natural demands of a social world than the samples of the other countries.